2021
DOI: 10.3390/app11093738
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Lensed Optical Fibers for Biosensing Probes Using CO2 and Femtosecond Lasers

Abstract: We propose a new method for precisely fabricating a lensed fiber with a desired focal length by first cleaving a coreless silica fiber using an ultrafast femtosecond laser without thermal effects and subsequently shaping the radius of curvature at the optical-fiber end using a CO2 laser. The precisely cleaved segment of the coreless silica fiber obtained with the femtosecond laser is attached to a long single-mode fiber. The beam-exposure time and laser power of the CO2 laser are adjusted to melt the coreless-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, optical sensing and optical imaging require optical fibers to have the ability to regulate light with the development of optical fiber technology, and the most optical fibers are difficult to meet present requirement of optical sensing and optical imaging. To solve this problem, photonic crystal fibers [7][8][9] and lens fibers [10][11][12] are developed, photonic crystal fiber can achieve different light regulation by changing different lattice parameters, and lens fiber can regulate light output and imaging by manufacturing optical lens on the end face of optical fiber. Although photonic crystal fiber and lens fiber have excellent light regulation ability, which have the disadvantages of complex fabrication, high cost and high requirements for equipment.…”
Section: Introductionmentioning
confidence: 99%
“…However, optical sensing and optical imaging require optical fibers to have the ability to regulate light with the development of optical fiber technology, and the most optical fibers are difficult to meet present requirement of optical sensing and optical imaging. To solve this problem, photonic crystal fibers [7][8][9] and lens fibers [10][11][12] are developed, photonic crystal fiber can achieve different light regulation by changing different lattice parameters, and lens fiber can regulate light output and imaging by manufacturing optical lens on the end face of optical fiber. Although photonic crystal fiber and lens fiber have excellent light regulation ability, which have the disadvantages of complex fabrication, high cost and high requirements for equipment.…”
Section: Introductionmentioning
confidence: 99%
“…In general, ultrafast laser refers to a pulse width of fewer than 10 ps, with several advantages, such as use in multi-material applications, high peak power density, and small heat-affected zone. Because of this, the ultrafast laser plays an important and extensive role in micro and nano-manufacturing [14]. Kim et al [15] reported a novel process to directly inscribe an FZPL on the cleaved facet of a stiff clad polymer fiber using a femtosecond pulsed laser in binary optical devices.…”
Section: Introductionmentioning
confidence: 99%